2015
DOI: 10.1371/journal.pone.0122956
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Heterogeneity of the β-Globin Gene in Various Geographic Populations of Yunnan in Southwestern China

Abstract: ObjectivesThe aim of this study was to investigate the geographic distribution of β-globin gene mutations in different ethnic groups in Yunnan province.MethodsFrom 2004 to 2014, 1,441 subjects with hemoglobin disorders, identified by PCR-reverse dot blot and DNA sequencing, were studied according to ethnicity and geographic origin. Haplotypes were examined among 41 unrelated thalassemia chromosomes.ResultsEighteen β-thalassemia mutations and seven hemoglobin variants were identified for 1,616 alleles in 22 dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…In addition to Hb E, the β-globin mutations reported in this study, i.e. CD 17 (A-T), CD 41/42 (-TTCT), and nucleotide -28 (A-G), were also similar to those reported in neighboring countries [5,[19][20][21] . Interaction of these abnormal genes can lead to several complex thalassemia syndromes, reflecting the serious health burden within the country.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to Hb E, the β-globin mutations reported in this study, i.e. CD 17 (A-T), CD 41/42 (-TTCT), and nucleotide -28 (A-G), were also similar to those reported in neighboring countries [5,[19][20][21] . Interaction of these abnormal genes can lead to several complex thalassemia syndromes, reflecting the serious health burden within the country.…”
Section: Discussionsupporting
confidence: 84%
“…Recent hospital-based studies on individuals undergoing a premarital health check or prenatal examination reported that HbE was the most prevalent mutation of HBB gene in populations from southwestern Yunnan, especially in minority groups such as Chinese Thai (Dai), Jingpo, and Achang (He et al, 2016;Zhang et al, 2015). In this study, a total of 1488 individuals from seven minority groups from Yunnan province were studied.…”
Section: Discussionmentioning
confidence: 99%
“…To accurately reconstruct haplotypes associated with b E -and b A -globin genes, individuals with other common beta thalassemia mutations in Yunnan including CD17, CD41-42, and IVS-II-654 (Zhang et al, 2015), and individuals who were compound heterozygotes for HbE/b-thalassemia, were excluded from the haplotype analysis. After excluding subjects with missing genotypes for any restriction site, the haplotypes of the seven polymorphic sites for both the b E and b A bearing chromosomes were identified using the population genetics data analysis package Arlequin V3.5.2 (Excoffier and Lischer, 2010).…”
Section: Detection Of Hbe and Haplotype Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Although δ‐thalassemia has no clinical significance, the disrupted function of δ‐globin may lead to aberrant measurements of Hb A 2 , and may complicate the diagnosis of β‐thalassemia when relying on the Hb A 2 measurements of the patient (Amirian et al, ). β‐Thalassemia is highly prevalent in Yunnan, China, and has a high genetic heterogeneity (Zhang et al, ). Identification of the clinical and hematological phenotypes of these causative mutations and their relative frequency in the population can improve our understanding of broader patterns across human populations.…”
Section: Introductionmentioning
confidence: 99%